2019
DOI: 10.1021/acs.langmuir.9b01300
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence-Induced Swift Jumping of Nanodroplets on Curved Surfaces

Abstract: In this work, we use molecular dynamics simulations to investigate coalescence-induced jumping of nanodroplets on curved surfaces with different wettabilities. On a curved surface, a liquid bridge will first form between two coalescing droplets as on a flat surface. However, contrary to symmetry-breaking-induced jumping on a flat surface, coalescing droplets would jump earlier than the liquid bridge gets into contact with the curved surface. Such an early symmetry breaking is induced by the opposite motion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Wang et al reported a millimetric triangular prism macrotexture and achieved a maximum droplet jumping velocity V j * = 0.53, with an energy conversion efficiency η ≈ 22.49% . In addition, rectangular ridge structures, curved surfaces, hydrophobic fibers, strings, and V-shaped structures , have been used to obtain a higher jumping velocity and break the velocity limit. Furthermore, Yuan et al used the impact between the liquid bridge and the bottom, flank side of the L-shaped macrotexture.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported a millimetric triangular prism macrotexture and achieved a maximum droplet jumping velocity V j * = 0.53, with an energy conversion efficiency η ≈ 22.49% . In addition, rectangular ridge structures, curved surfaces, hydrophobic fibers, strings, and V-shaped structures , have been used to obtain a higher jumping velocity and break the velocity limit. Furthermore, Yuan et al used the impact between the liquid bridge and the bottom, flank side of the L-shaped macrotexture.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Xie et al patterned a single nanometric rectangular ridge to enhance nanodroplet jumping velocity; molecular dynamics simulations showed that the maximum jumping velocity was 1.81 times higher than the nanoscale velocity limit . Besides that, curved surface and hydrophobic fibers ,, have also been used to successfully enhance the jumping velocity of microdroplets.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the jumping efficiency of micron- and millimeter-scale droplets can be significantly tuned by constructing ridges, microgrooves, , and egg tray-like structures on superhydrophobic surfaces. The research on nanoscale droplet confluence by molecular dynamics simulations also shows that the jumping velocity can be significantly increased by constructing individual grooves, ridges, or more hydrophobic strips on the superhydrophobic surface with dimensions comparable to the radius of the coalescing droplets. , The above study analyzed the mechanism of enhancing droplet jumping velocity by geometric structures and confirmed that macroscopic structures can effectively enhance the efficiency of coalescence-induced droplet jumping, but this is still a long way from achieving large-scale efficient droplet jumping. On the one hand, previous studies have focused on the jumping of individual droplets, usually studying only the effect of individual macroscopic structures on droplet jumping, which cannot be directly applied to large scales.…”
Section: Introductionmentioning
confidence: 84%